A paper-based colorimetric molecular test for SARS-CoV-2 in saliva - Josiah Levi Davidson; Jiangshan Wang; Murali Kannan Maruthamuthu; Andres Dextre; Ana Pascual-Garrigos; Suraj Mohan; Sai Venkata Sravan Putikam; Fujr Osman Ibrahim Osman; Darby McChesney; Jordan Seville; Mohit S. Verma (Biosensors and Bioelectronics: X, 2021)
Herein, we describe the development of a paper-based device to detect nucleic acids of pathogens of interest in complex samples using loop-mediated isothermal amplification (LAMP) by producing a colorimetric response visible to the human eye. To demonstrate the utility of this device in emerging public health emergencies, we developed and optimized our device to detect SARS-CoV-2 in human saliva without preprocessing. The resulting device was capable of detecting the virus within 60 min and had an analytical sensitivity of 97% and a specificity of 100% with a limit of detection of 200 genomic copies/μL of patient saliva using image analysis. The device consists of a configurable number of reaction zones constructed of Grade 222 chromatography paper separated by 20 mil polystyrene spacers attached to a Melinex® backing via an ARclean® double-sided adhesive. The resulting device is easily configurable to detect multiple targets and has the potential to detect a variety of pathogens simply by changing the LAMP primer sets.